Attitudes and behaviors of household food waste among university students in Milan, Italy: the UniFoodWaste study protocol - Catalini, Alessandro; Stacchini, Lorenzo; Nucci, Daniele; Passeri, Chiara; Romano, Nicoletta; Ferranti, Roberta; Bonassi, Gaia; Gianfredi, Vincenza (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Food waste is a pressing global issue with significant economic, environmental, and social implications. This protocol outlines an observational cross-sectional study aimed at assessing attitudes and behaviors related to household food waste among Italian university students. Methods: The study will involve the administration of a self-administered, online, anonymous questionnaire to university students enrolled at the University of Milan. Data collection will encompass socio-demographic characteristics, household food waste behaviors, lifestyle factors (such as physical activity, alcohol consumption, and diet), and health-related outcomes (including self-related health, eating disorders, alcohol use disorders, and depressive symptoms). The online questionnaire will be implemented using Microsoft Forms. All data will be self-reported, with participation being voluntary. Results: Anticipated results include insights into the prevalence of food waste behaviors among university students, associations with demographic and lifestyle factors, and potential impacts on health outcomes. Our study aims to provide a comprehensive understanding of the factors influencing household food waste among Italian university students by employing an epidemiological approach to understanding these behaviours over time and space. Conclusions: In conclusion, this study will contribute to filling gaps in knowledge within the scientific community, inform public health policies, and promote sustainable food consumption practices among young adults.